Assessment of E-Banking Services and Legal Framework in Albania - Teliti, Ersida; Mersini, Rezarta (Mediterranean Journal of Social Sciences, 2012)
Continuous advancements in information technology have led to a broad range of banking products and services.Among all types of e-banking, internet banking provides faster, cheaper and timeless services via internet. Financial institutionsin developing countries should be aware of the advantages of online banking in terms of convenience, flexibility, competitiveadvantage and lower costs. This paper reveals the current expansion of e-banking in Albania by reviewing existing transactionalsites and latest financial reports. Furthermore, e-banking legal framework in Albania has been analyzed with conclusions beingreached. The study suggests that the actual legal framework needs further improvement and should be compliant to the EU legalframework, and that a public informing campaign should be raised with regards to electronic payment instruments. A recentsurvey has been carried out to collect data from the Albanian banks offering e-banking services. The survey identifies theimportant role of e-banking in gaining competitive advantage with lower costs. It implies that financial institutions in Albania haveto make strategic plans in order to improve e-banking services and online marketing.